Heat Priming Induces Trans-generational Tolerance to High Temperature Stress in Wheat - Wang, Xiao; Xin, Caiyun; Cai, Jian; Zhou, Qin; Dai, Tingbo; Cao, Weixing; Jiang, Dong (Frontiers in Plant Science, 2016)
Wheat plants are very sensitive to high temperature stress during grain filling. Effects of heat priming applied to the first generation on tolerance of the successive generation to post-anthesis high temperature stress were investigated. Compared with the progeny of non-heat primed plants (NH), the progeny of heat-primed plants (PH) possessed higher grain yield, leaf photosynthesis and activities of antioxidant enzymes and lower cell membrane damage under high temperature stress. In the transcriptome profile, 1430 probes showed obvious difference in expression between PH and NH. These genes were related to signal transduction, transcription, energy, defense, and protein destination and storage, respectively. The gene encoding the lysine-specific histone demethylase 1 (LSD1) which was involved in histone demethylation related to epigenetic modification was up-regulated in the PH compared with NH. The proteome analysis indicated that the proteins involved in photosynthesis, energy production and protein destination and storage were up-regulated in the PH compared with NH. In short, thermos-tolerance was induced through heritable epigenetic alternation and signaling transduction, both processes further triggered prompt modifications of defense related responses in anti-oxidation, transcription, energy production, and protein destination and storage in the progeny of the primed plants under high temperature stress. It was concluded that trans-generation thermo-tolerance was induced by heat priming in the first generation, and this might be an effective measure to cope with severe high-temperature stresses during key growth stages in wheat production.